Characteristics of the scientific researches in sport climbing (review of the monographs). - Sedliar Yu.V (Kharkov National Pedagogical University, 2011)
It is presented analysis of monographs, in which considered the questions of preparation sport climbing athlete. It is defined the level of development of different theoretical and practical aspects in this sphere. For the most developed aspects of the process of preparation in sport climbing belong the categories of physical preparation. A great number of recommendations were direct on reporting of the problems of force preparation and endurance. For development of flexibility and coordination is belonging less attention.